David G. Horrell. Ethnicity and Inclusion: Religion, Race, and Whiteness in Constructions of Jewish and Christian Identities - Joslyn-Siemiatkoski, Daniel (Studies in Christian-Jewish Relations, 2023)
No abstract is available.